Heritability of the Symbiodinium community in vertically- and horizontally-transmitting broadcast spawning corals - Kate M. Quigley (Nature Portfolio, 2017)
Abstract The dinoflagellate-coral partnership influences the coral holobiont’s tolerance to thermal stress and bleaching. However, the comparative roles of host genetic versus environmental factors in determining the composition of this symbiosis are largely unknown. Here we quantify the heritability of the initial Symbiodinium communities for two broadcast-spawning corals with different symbiont transmission modes: Acropora tenuis has environmental acquisition, whereas Montipora digitata has maternal transmission. Using high throughput sequencing of the ITS-2 region to characterize communities in parents, juveniles and eggs, we describe previously undocumented Symbiodinium diversity and dynamics in both corals. After one month of uptake in the field, Symbiodinium communities associated with A. tenuis juveniles were dominated by A3, C1, D1, A-type CCMP828, and D1a in proportional abundances conserved between experiments in two years. M. digitata eggs were predominantly characterized by C15, D1, and A3. In contrast to current paradigms, host genetic influences accounted for a surprising 29% of phenotypic variation in Symbiodinium communities in the horizontally-transmitting A. tenuis, but only 62% in the vertically-transmitting M. digitata. Our results reveal hitherto unknown flexibility in the acquisition of Symbiodinium communities and substantial heritability in both species, providing material for selection to produce partnerships that are locally adapted to changing environmental conditions.